SALES PROMOTION MESSAGE APPEAL AND BRAND AMBASSADOR EFFECTS TOWARD TOKOPEDIA’S PURCHASE INTENTION - Justyne Artha Thehawijaya; Daniel Susilo (Lafadz Jaya Publisher, 2023)
Companies nowadays attracts more customers by holding Sales Promotion. For the record, Tokopedia has been known as the most accessed E-commerce in Indonesia also holds Sales Promotion event frequently using their Instagram. Furthermore, Tokopedia is also going hand in hand with the world’s biggest boyban, BTS to attract more audiences on a wider scale. The Objective of this research is to find out the react of Sales Promotion and Brand Ambassador towards Purchase Intention of free delivery fee products of Tokopedia and the percentage of the react. The method used on this research are quantitative explanator with positivism paradigm and purposive sampling technique. This thesis is being analysed by using SPSS statistic method. The result of this study indicates the influence of sales promotion message appeal and BTS as brand ambassador on the purchase intention of WIB Sale products by 49,8%.